The saplings vegetation and environmental factors in Malempo Hamlet of Mallawa Resort, Bantimurung Bulusaraung National Park - Zainuddin, Dian Utami (Anjoro: International Journal of Agriculture and Business, 2021)
This study aimed to determine the composition and structure of sapling vegetation and the relationship of environmental factors with the structure of the vegetation in Malempo Hamlet of Mallawa Resort, Bantimurung Bulusaraung National Park, Maros Regency, which is in three regions of direction, namely South, North, and West. Laying transects were conducted randomly in each regional direction with 5 replications. Each transect was 100 × 5 meters in size, for the tree saplings, in wich they were provided with 5 × 5 meters for 10 plots alternatingly placed. Data collection of vegetation was conducted in the plot by counting the number of each species of tree saplings and determine the canopy space-filling. The composition of sapling vegetation was found 39 species from 28 families. The species of sapling tree with the highest structure of sapling vegetation in the study area based on density, frequency, dominance, and IVI is Celtis philippensis, Ardisia elliptica, Leea indica, Saurauia nudiflora, and Phytocrene macrophylla and the lowest are Cordyline fruticosa, Caryota mitis, Calamus asperrimus, and Arenga pinnata. The canopy, altitude, soil percentage without vegetation, and slope declivity have a relationship with the structure of sapling vegetation.